Association between sex steroid hormones and subsequent hyperglycemia during pregnancy - Meng, Ying; Thornburg, Loralei L.; Hoeger, Kathleen M.; Núñez, Zorimar Rivera-; Kautz, Amber; Evans, Adam T.; Wang, Christina; Miller, Richard K.; Groth, Susan W.; O’Connor, Thomas G.; Barrett, Emily S. (Frontiers in Endocrinology, 2023)
Objective: Sex steroid hormones may play a role in insulin resistance and glucose dysregulation.However, evidence regarding associations between early-pregnancy sex steroid hormones and hyperglycemia during pregnancy is limited. The primary objective of this study was to assess the relationships between first trimester sex steroid hormones and the subsequent development of hyperglycemia during pregnancy; with secondary evaluation of sex steroid hormones levels in mid-late pregnancy, concurrent with and subsequent to diagnosis of gestational diabetes.Methods: Retrospective analysis of a prospective pregnancy cohort study was conducted.Medically low-risk participants with no known major endocrine disorders were recruited in the first trimester of pregnancy (n=319). Sex steroid hormones in each trimester, including total testosterone, free testosterone, estrone, estradiol, and estriol, were assessed using highperformance liquid chromatography and tandem mass spectrometry. Glucose levels of the 1-hour oral glucose tolerance test and gestational diabetes diagnosis were abstracted from medical records. Multivariable linear regression models were fitted to assess the associations of individual first trimester sex steroids and glucose levels.In adjusted models, first trimester total testosterone (β=5.24, 95% CI: 0.01, 10.46, p=0.05) and free testosterone (β=5.98, 95% CI: 0.97, 10.98, p=0.02) were positively associated with subsequent glucose concentrations and gestational diabetes diagnosis (total testosterone: